Remarks on the Particular Behavior in Martensitic Phase Transition in Cu-Based and Ni-Ti Shape Memory Alloys - Torra, Vicenç (2018)
Many macroscopic behaviors of the martensitic transformations are difficult to explain in the frame of the classical first-order phase transformations, without including the role of point and crystallographic defects (dislocations, stacking faults, interfaces, precipitates). A few major examples are outlined in the present study. First, the elementary reason for thermoelasticity and pseudoelasticity in single crystals of Cu–Zn–Al (β-18R transformation) arises from the interaction of a growing martensite plate with the existing dislocations in the material. Secondly, in Cu–Al–Ni, the twinned hexagonal (γ′) martensite produces dislocations inhibiting this transformation and favoring the appearance of 18R in subsequent transformation cycles. Thirdly, single crystals of Cu–Al–Be visualize, via enhanced stress, a transformation primarily to 18R, a structural distortion of the 18R structure, and an additional transformation to another martensitic phase (i.e., 6R) with an increased strain. A dynamic behavior in Ni–Ti is also analyzed, where defects alter the pseudoelastic behavior after cycling.